Normativnost osrednjega slovenskega knjižnega jezika od 16. do 19. stoletja - Orel, Irena (Slavistična revija, 2010)
The article presents the 16th century literary norm vis-a-vis the norm of the Enlightment period at the end of the 18th century, as is evident from the phonology in certain typical morphonological variatns in the translations of the New Testament and psalms by both 16th century translators, P. Trubar and J. in ! J. Dalmatin, as well as by the Upper Carniolan translators J. Japelj and B. Kumerdej, 200 years later; in temporally and thematically different texts by M. Pohlin and in secular texts by A. T. Linhart, B. Kumerdej, and V. Vodnik from the end of the 18th and the beginning of the 19th centuries. The author aims to examine to what extand the level of normativity or linguistic change depends on the type of text and not only on the author's individual usage and views, the region of his origin, or his idiom.
Keywords: 16./19.st.; Age of Enlightenment; knjižna norma; knjižni jezik; morfonologija; Protestantism; protestantizem; razsvetljenstvo; Slovene; slovenščina; standard language; zgodovina slovenskega jezika